2022
DOI: 10.1021/acs.langmuir.1c02935
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Optoelectronic Properties of Ultrathin Trigonal Selenium: A Density Functional Theory Study with van der Waals Correction

Abstract: Selenium is an important earth-abundant and nontoxic semiconductor with numerous applications across semiconductor industries. Selenium has drawn attention from scientific communities for photovoltaics and imaging devices. Its usage as a photosensitive material largely involves the synthesis of the amorphous phase (a-Se) via various experimental techniques. However, the ground state crystalline phase of this material, the trigonal selenium (t-Se), a layered van der Waals solid, has not been extensively studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Figure 3(b) is the x-ray diffraction pattern of Se powder. By means of the analysis of the diffraction peaks, we can determine that the crystalline phase structure is typical of the t-Se phase, which further proves the crystal structure of Se powder [30]. Figure 4(a) insert demonstrates the energy-dispersive x-ray spectroscopy image of Se powder.…”
Section: Preparation and Characterizationmentioning
confidence: 66%
See 1 more Smart Citation
“…Figure 3(b) is the x-ray diffraction pattern of Se powder. By means of the analysis of the diffraction peaks, we can determine that the crystalline phase structure is typical of the t-Se phase, which further proves the crystal structure of Se powder [30]. Figure 4(a) insert demonstrates the energy-dispersive x-ray spectroscopy image of Se powder.…”
Section: Preparation and Characterizationmentioning
confidence: 66%
“…t-Se is the most stable crystal structure with the highest anisotropy. It is a semiconducting solid, consisting of helical chains of covalently bound Se atoms and relatively weak van der Waals forces between the chains [27][28][29][30]. These provide the possibility for the preparation of Se nanosheets using the liquid phase exfoliation (LPE) method.…”
Section: Introductionmentioning
confidence: 99%
“…The X‐ray diffraction (XRD) patterns for the samples under study are shown in Figure . The figure illustrates the standard reflections from monoclinic selenium (a=12.850.28emnormalÅ,b=8.070.28emnormalÅ,c=9.130.28emnormalÅ$a = 12.85\;\hbox{\AA}, b = 8.07\;\hbox{\AA}, c = 9.13\;\hbox{\AA}$, β=93.31o$\beta = 93.31^{\rm o}$ [ 10,11 ] ), trigonal selenium (a=b=4.3660.28emnormalÅ,c=4.9540.28emnormalÅ,γ=120o$a = b = 4.366\;\hbox{\AA}, c = 4.954\;\hbox{\AA}, \gamma = 120^{\rm o}$ [ 12 ] ), and hexagonal Mg (a=3.2090.28emnormalÅ,c=5.210.28emnormalÅ$a = 3.209\;\hbox{\AA}, c = 5.21\;\hbox{\AA}$ [ 13 ] ). The X‐ray diffraction patterns for the MgSe pellets pressed at 100 bars before and after being welded with laser are also shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray diffraction (XRD) patterns for the samples under study are shown in Figure 3. The figure illustrates the standard reflections from monoclinic selenium (a = 12.85 Å, b = 8.07 Å, c = 9.13 Å, 𝛽 = 93.31 o [10,11] ), trigonal selenium (a = b = 4.366 Å, c = 4.954 Å, 𝛾 = 120 o [12] ), and hexagonal Mg (a = 3.209 Å, c = 5.21 Å [13] ). The X-ray diffraction patterns for the MgSe pellets pressed at 100 bars before and after being welded with laser are also shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, crystalline Se capping topological insulators (TI) showed improved capability to preserve the intrinsic transport properties of TI in comparison with amorphous Se (Lin et al, 2018 ). In addition, Barman et al ( 2022 ) recently observed high optical absorption coefficient and favourable transport properties of t‐Se ultrathin films, which make t‐Se attractive for the fabrication of photosensitive detector devices. Not only industrially, but also from an environmental point of view, crystalline Se has been described to be highly settleable and therefore more prone for separation/recovery than a‐Se (Lenz et al, 2009 ).…”
Section: Towards Circular Economy: Applications Of the Different Se A...mentioning
confidence: 99%